Nanoemulsification of Satureja khuzestanica essential oil and pure carvacrol; comparison of physicochemical properties and antimicrobial activity against food pathogens. (February 2019) - Mazarei, Zeinab; Rafati, Hasan
Abstract: The aim of the present study was to fabricate a stable carvacrol-rich Satureja khuzestanica essential oil (SKEO) nanoemulsion and evaluate its antibacterial activity against food borne pathogens. The effect of determining factors including preparation method, surfactant type, surfactant to oil ratio and hydrophilic lipophilic balance (HLB) were evaluated on the mean particle size and stability of nanoemulsions. The optimized formulation prepared by high speed homogenization method containing 3%w/w EO and 9%w/w surfactant mixture (Tween 80 + Span 80) with HLB value of 10 that produced stable nanoemulsion with mean particle diameter of 95 nm. The defined conditions were applied for fabrication of pure carvacrol nanoemulsion. Both formulations showed appreciable long-term stability. The antibacterial activity of pure SKEO, carvacrol and their nanoemulsions were examined against three food-borne bacteria. The results showed an improvement in antibacterial activity for carvacrol and SKEO nanoemulsions against Salmonella enterica and Staphylococcus aureus . Graphical abstract: Image 1 Highlights: SKEO: Satureja khuzestanica essential oil, HLB: hydrophilic lipophilic balance. Stable nanoemulsions were fabricated from carvacrol and SKEO. The best surfactants mixture defined as Tween 80: Span 80 with HLB value of 10. Ostwald ripening was inhibited by optimization of HLB value of surfactants. The MIC value of nanoemulsions improved 2–4 times compared to the bulk oils in two strains.